PENERAPAN PENDEKATAN VALUE CLARIFICATION TECHNIQUE (VCT) DALAM MENINGKATKAN HASIL BELAJAR DI SMA NEGERI 1 TIKKE RAYA KAB. MAMUJU UTARA - Nalva, Mulkul Farisa; T., M. Yusuf; Amri, Muhammad (Universitas Islam Negeri Alauddin Makassar, 2019)
ABSTRACTThis quantitative type of research was conducted on 47 students of class XI Science in SMA Negeri 1 Tikke Raya with a random sampling technique that is random, where all members of the population were not sampled but the population was randomly drawn by researchers to be drawn into samples, observations and test items as a research instrument, to obtain data that is processed and analyzed with statistical techniques, both descriptive statistics and inferential statistics. Through data analysis, it was concluded that: 1) Learning outcomes of Islamic Religious Education before applying the VCT approach with an average student score of 80, 2) Learning outcomes of Islamic Religious Education after applying the VCT approach with an average student score of 85, and 3 ) Hypothesis testing results about the Effectiveness of the Application of the Value Clarification Technique (VCT) Approach to Learning Outcomes of Islamic Education in SMA Negeri 1 Tikke Raya Kab. North Mamuju, By testing the significance it can be concluded that t-test (t0) = 6.033 and t-table = 2.014. Because t-test> t-table, H0 is rejected, Ha is accepted. That is, there is an influence of the application of the VCT approach to the Learning Outcomes of Islamic Education Class XI science students in SMA Negeri 1 Tikke Raya Kab. North Mamuju.